Sources of organic trace minerals in diets for weaned piglets - Mello, Gabriela de [UNESP]; Berto, Dirlei Antonio [UNESP]; Lo Tierzo, Vivian [UNESP]; Augusto, Regina Maria Nascimento [UNESP]; Silva, Anália Maria Ribeiro da; Trindade Neto, Messias Alves da; Villela, Cássio Cordeiro Ensá Junqueira [UNESP]; Girão, Lúcio Vilela Carneiro [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
One hundred and twenty six piglets from a commercial genetic strain weaned at 21 days of age (6.11±0.42 kg) were used to evaluate the effects of supplementation levels of organic sources of trace minerals in the diets of weaned piglets on performance, occurrence of diarrhea, excretion of copper and zinc in the feces, and hematological parameters. A completely randomized block design was adopted, composed of six treatments (diets containing 100% of inorganic trace minerals premix at 3.00 kg/T; diets containing 0, 25, 50, 75 or 100% of organic trace minerals premix, equivalent to 0; 0.75; 1.50; 2.25 or 3.00 kg/T, respectively), seven replicates and three animals per plot. During the experimental period (from 21 to 63 days of age), the increasing levels of organic trace minerals premix in the diets determined a quadratic effect on daily weight gain (DWG), feed conversion (FC), percentage of hematocrit (Ht), hemoglobin (Hb), mean corpuscular hemoglobin (MCH), mean corpuscular volume (MCV), platelets (Pt), and a linear increase of Cu and Zn concentrations in feces. The comparison of means between the treatment with inorganic trace minerals premix and the other treatments showed that piglets fed diets without trace minerals premix had lower values of DWG, Ht, Hb, MCH, MCV, Pt and the worst FC value of piglets fed diets containing 25% of organic trace minerals premix presented lower values of Ht and Hb, in comparison with those fed diets with 100% of inorganic trace minerals premix. Inorganic trace minerals premix can be substituted by organic trace minerals premix at a lower level of inclusion in diets for weaned piglets.
Keywords: diarrhea; hematological parameters; pigs; performance